Capital letters: Hugo, Baudelaire, Camus, and the death penalty - Morisi, Ève (FlashPoints, 2020)
Introduction. Three writers and a punishment -- New abolitionist poetics: Hugo's Le dernier jour d'un condamn? -- The death penalty, from representation to expression -- Pain and punishment: the guillotine's torture -- Words that kill in Baudelaire -- Prose praising sacrifice: Hugo, Maistre, and beyond -- Poeticized slaughter? Execution in Les fleurs du mal -- Camus's capital fiction and literary responsibility -- Ad nauseam: Camus's narrative roads to abolitionism -- Poetic accountability: critical language and its limits -- Conclusion: Ink and the scaffold.